A broadband FSS bandstop filter in terahertz region - Sarkar S.; Chakrabarti T.; Ghosh S.K.; Bhattacharyya S. (My University, 2025)
A wideband bandstop filter using frequency selective surface (FSS) operating in the terahertz (THz) frequency range has been reported. The simulation results show that it has a 3-dB bandwidth of 22.9 THz over the resonating frequency of 24.1 THz. The transmission stopband lesser than 30dB has been achieved along with a fractional bandwidth of 95%. The structure has been analyzed under the variations of several geometrical parameters. The structure is found to behave as wideband stopband filter till 40o incident angle. The structure offers wide stopband till 15o polarization angle. Being ultra-thin (~/12) and simple in nature, the filter can be very easy to realize in practice. The structure finds its application in spectroscopy, imaging etc. © 2019 URSI. All rights reserved.